1991
DOI: 10.4319/lo.1991.36.3.0468
|View full text |Cite
|
Sign up to set email alerts
|

Organic volatile sulfur in lakes of the Canadian Shield and its loss to the atmosphere

Abstract: Identities, concentrations, and fluxes of volatile sulfur compounds (VSCs) were determined in 11 lakes in northwestern Ontario. Carbonyl sulfide (COS: up to 1.1 nM) and dimethyl sulfide (DMS: up to 11 nM) were present in surface waters during most of the ice-free season. Depth profiles showed accumulations below the mixed layer of methane thiol (MSH), DMS, and dimethyl disulfide (DMDS). There was no effect of low pH or increased [SOd2-] (from 2.4 to 12.3 mg liter-') on the concentrations and identities of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…This might be due to more efficient mixing in the ocean surface waters compared to lakes. However, Richards et al (1991) found that the concentration remained at the same level throughout the water 20 column and observed a midsummer OCS concentration minima in 8 of the 11 studied lakes. This latter point was surprising because photochemical production should be highest during the summer months.…”
Section: Lakes and Riversmentioning
confidence: 83%
See 2 more Smart Citations
“…This might be due to more efficient mixing in the ocean surface waters compared to lakes. However, Richards et al (1991) found that the concentration remained at the same level throughout the water 20 column and observed a midsummer OCS concentration minima in 8 of the 11 studied lakes. This latter point was surprising because photochemical production should be highest during the summer months.…”
Section: Lakes and Riversmentioning
confidence: 83%
“…Richards et al (1991) calculated OCS flux from the different lakes in Ontario, Canada, based on concentration measurements and wind-speed-dependent gas transfer coefficient, resulting in fluxes of 2-5 pmol OCS m -2 s -1 . In another study, Richards et al (1994) found fluxes of 2-34 pmol OCS m -2 s -1 in salty lakes.…”
Section: Lakes and Riversmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission factors applied here for H 2 S and DMS from freshwater lakes (see Appendix A) in Canada were selected by taking values from the lower range of freshwater sulfur flux estimates derived from several studies including Richards et al (1991), Bates et al (1992), Giblin and Wieder (1992), Gröne (1997), Bodenbender et al (1999), and . A representative day of H 2 S and DMS emissions was created from these emission factors and the SMOKE default temporal profile for natural sources.…”
Section: Freshwatermentioning
confidence: 99%
“…b Approximate factor range for ocean DMS based on reallocation of annual sulfur values from Kloster et al (2006) to daily values. c Taken from values from the lower range of freshwater sulfur flux estimates derived from several studies including Richards et al (1991), Bates et al (1992), Giblin and Wieder (1992), Gröne (1997), Bodenbender et al (1999. d Given the lack of available information on natural emissions from the Great Salt Lake the H 2 S factor applied for freshwater lakes was conservatively applied.…”
Section: Appendix Amentioning
confidence: 99%